ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI NIAT UNTUK BERDONOR DARAH SECARA REGULER DI UTD PMI KABUPATEN BANTUL YOGYAKARTA - Francisca Romana Sri Supadmi; Nur’Aini Purnamaningsih; Rijantono Franciscus Maria (Universitas Jenderal Achmad Yani Yogyakarta, 2019)
Background: Blood supplies estimated to be around 2% of the total population1. However, only 1.88 million bags of blood can be met or 40% of the total needs, so there is a 60% lack of blood from the minimum requirement2. Objective: The purpose of this study was to analyze the factors that influence the intention to donate blood regularly at UTD PMI Bantul Regency Yogyakarta using the Theory of Planned Behavior (TPB) approach. Methods: This research was conducted at UTD PMI Bantul Regency, Yogyakarta in September-December 2018. The number of respondents was 35 voluntary blood donors, with sampling techniques using accidental sampling. Results: The results of multiple linear regression analysis show that attitudes, subjective norms, and behavioral control have a significant effect on the intention to donate. While the results of the regression analysis partially, based on a significant level of value, attitudes have a significant influence on one's intention in donating, while subjective norms and behavioral control do not significantly influence one's intentions in donating. Conclusion: The attitude had the most significant influence on the intention to donate regularly on UTD PMI Bantul Regency Yogyakarta using the Theory of Planned Behavior (TPB) approach.